An analytical model for baseflow recession considering riverbank permeability - Guoliang Wang; Xiuyu Liang (地质科技通报, 2023)
Objective Baseflow recession analysis is an effective approach to estimating watershed-scale hydrogeological parameters. However, the traditional baseflow recession model did not consider the effects of semipervious riverbanks, and their influence on parameter estimation is unclear. Methods To address this issue, a mathematical model for groundwater flow in an unconfined aquifer with time-dependent recharge and river stages is presented. The effects of the semipervious riverbank are specifically taken into consideration. The analytical solutions of the hydraulic head and discharge are derived by using Green's function method, and their validities are tested by numerical simulations. Results The results show that, forced by the fluctuating recharge rate, the lower riverbank permeability leads to a higher peak of hydraulic heads, a lower baseflow, and slower baseflow recessions. For the case forced by the fluctuating river stages, the lower riverbank permeability leads to the weaker responses of water flow to the fluctuated river stage and the lower fluxes of surface water-groundwater interaction. The riverbank permeability significantly affects the baseflow recession curves. During early stage, the low riverbank permeability caused the power index of the recession curve to be larger than 3. For later stage, the power index approaches 1, which is not affected by the riverbank permeability. Conclusion For a low riverbank permeability, the traditional model will overestimate the baseflow and underestimate the hydraulic conductivities of aquifers because it neglects the effects of riverbank permeability.